2022
DOI: 10.1038/s41531-022-00359-y
|View full text |Cite
|
Sign up to set email alerts
|

Specific gut microbiota alterations in essential tremor and its difference from Parkinson’s disease

Abstract: Essential tremor (ET) is the most common movement disorder and share overlapping symptoms with Parkinson’s disease (PD), making differential diagnosis challenging. Gut dysbiosis is regarded crucial in the pathogenesis of PD. Since ET patients also has comorbidity in gastrointestinal disorders, the relationship between gut microbiota and ET really worth investigating and may help distinguishing ET from PD. Fecal samples from 54 ET, 67 de novo PD and 54 normal controls (NC) were collected for 16S ribosomal RNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…Microbial DNA extraction was based on 200 mg samples and further puri ed using QIAamp ® Fast DNA Stool Mini Kit (QIAGEN, Hilden, Germany) following the manufacturer's instructions. The details of fecal bacterial sequencing (16S rRNA gene and qPCR quanti cation) were consistent with our previous study 47 . The high variable V3-V4 regions of 16S rRNA were ampli ed using 357F(5'-ACTCCTACGGRAGGCAGCAG-3') and 806R(5'-GGACTACHVGGGTWTCTAAT-3') bacterial primer pair with two-step amplicon library building on the Novaseq platform, according to the manual from Illumina for the overhang sequences and barcodes.…”
Section: Fecal Sample Collection and Sequencingsupporting
confidence: 86%
“…Microbial DNA extraction was based on 200 mg samples and further puri ed using QIAamp ® Fast DNA Stool Mini Kit (QIAGEN, Hilden, Germany) following the manufacturer's instructions. The details of fecal bacterial sequencing (16S rRNA gene and qPCR quanti cation) were consistent with our previous study 47 . The high variable V3-V4 regions of 16S rRNA were ampli ed using 357F(5'-ACTCCTACGGRAGGCAGCAG-3') and 806R(5'-GGACTACHVGGGTWTCTAAT-3') bacterial primer pair with two-step amplicon library building on the Novaseq platform, according to the manual from Illumina for the overhang sequences and barcodes.…”
Section: Fecal Sample Collection and Sequencingsupporting
confidence: 86%
“…Distorted α -syn clusters, also known as Lewy body depositions or deposits, play a role in the degeneration of neurons (dopaminergic) in the part of the brain known as substantia nigra (controls movements) and various other related functions that lead to the onset of several key non-motor and motor characteristics of Parkinson's disease (PD), such as dementia, tremor, bradykinesia, anxiety, digestive tract disability, rigidity, behavioral changes, and postural instability [ 15 ]. The concept of a “gut-brain axis,” a bidirectional communication mechanism between the enteric and central nervous systems and the digestive system, has been supported by the discovery of α -syn clusters in peripheral locations, including the enteric nervous system (ENS), despite their most frequent location in the brain [ 16 ].…”
Section: Neurodegeneration and Associated Diseasesmentioning
confidence: 99%
“…However, unlike PD, no significant gastrointestinal dysfunction was reported in ET patients compared with controls [33]. In a more recent study, Zhang et al demonstrated that patients with ET showed altered gut microbiota in an ET group compared with PD groups, indicating a difference in gut dysbiosis between ET and PD [34]. Overlapping clinical features between PD and ET make it challenging to discriminate between them, especially for early PD.…”
Section: Discussionmentioning
confidence: 99%